Target genes, variants, tissues and transcriptional pathways influencing human serum urate levels - Tin, Adrienne; Marten, Jonathan; Halperin Kuhns, Victoria L; Li, Yong; Wuttke, Matthias; Kirsten, Holger; Sieber, Karsten B; Qiu, Chengxiang; Gorski, Mathias; Yu, Zhi; Giri, Ayush; Sveinbjornsson, Gardar; et al. (Nature genetics, 2019)
Elevated serum urate levels cause gout and correlate with cardiometabolic diseases via poorly understood mechanisms. We performed a trans-ancestry genome-wide association study of serum urate in 457,690 individuals, identifying 183 loci (147 previously unknown) that improve the prediction of gout in an independent cohort of 334,880 individuals. Serum urate showed significant genetic correlations with many cardiometabolic traits, with genetic causality analyses supporting a substantial role for pleiotropy. Enrichment analysis, fine-mapping of urate-associated loci and colocalization with gene expression in 47 tissues implicated the kidney and liver as the main target organs and prioritized potentially causal genes and variants, including the transcriptional master regulators in the liver and kidney, HNF1A and HNF4A. Experimental validation showed that HNF4A transactivated the promoter of ABCG2, encoding a major urate transporter, in kidney cells, and that HNF4A p.Thr139Ile is a functional variant. Transcriptional coregulation within and across organs may be a general mechanism underlying the observed pleiotropy between urate and cardiometabolic traits.
Keywords: játra; celogenomová asociační studie; signální transdukce; Signal Transduction; Uric Acid; hepatocytární jaderný faktor 1-alfa; kardiovaskulární nemoci; Polymorphism, Single Nucleotide; nádorové proteiny; Humans; ATP Binding Cassette Transporter, Subfamily G, Member 2; Metabolic Diseases; kohortové studie; genetické lokusy; genetické markery; ledviny; jednonukleotidový polymorfismus; Organ Specificity; Kidney; lidé; kyselina močová; hepatocytární jaderný faktor 4; Cohort Studies; dna (nemoc); Gout; Liver; Cardiovascular Diseases; metabolické nemoci; Hepatocyte Nuclear Factor 4; Genetic Predisposition to Disease; genetická predispozice k nemoci; Genetic Markers; Genome-Wide Association Study; Hepatocyte Nuclear Factor 1-alpha; Neoplasm Proteins; orgánová specificita; ABC transportér z rodiny G, člen 2; Genetic Loci